Pelatihan Kewirausahaan Secara Daring untuk Meningkatkan Motivasi Berwirausaha Siswa-Siswi MA Ishlahul Amanah - Desri Kristina Silalahi; Bandiyah Sri Aprillia; Kharisma Bani Adam (Penerbit Goodwood, 2023)
Purpose: The students of MA Islahul Amanah are the next generation of the nation who must take their steps to reach the future. Most of them have constraints in terms of costs to continue on to higher education. Thus, a motivation or direction is needed for MA Ishlahul Amanah students about entrepreneurship. Entrepreneurship is the right alternative choice to overcome unemployment. This is to encourage them to be more independent after completing their school education. At least they are not a burden to their parents, but can help their family's economy Methodology/approach: The methods used are: (1) condition survey; (2) team conciliation to discuss the activities carried out; (3) preparation to determine the implementation time and equipment to be prepared; (4) implementing activities by conducting online entrepreneurship training; (5) evaluation of activities to measure the achievement of activities with a questionnaire. Results/findings: Participants receive tips on building start-ups, namely innovating business ideas, creating business models, raising capital, inviting like-minded people to maintain service/product quality and